Isotropic and anisotropic elastic scatterers of underwater sound - Alexandr A. Kleschev (Krylov State Research Centre, 2021)
Object and purpose of research. This paper discusses diffraction parameters of isotropic and anisotropic elastic scatterers, demonstrating that transversally isotropic bodies with a certain orientation of their planes of isotropy might be regarded as isotropic scatterers with similar size, shape and physical parameters. Subject matter and methods. Diffraction theory methods in solution of boundary problems and equations of dynamic elasticity theory for isotropic and anisotropic bodies. Main results. Calculation of moduli for angular parameters, as well as of relative back-scattering sections for isotropic and anisotropic scatterers of various shapes. Conclusion. The studies demonstrated that if transversally isotropic bodies of various shapes have a certain orientation of their planes of isotropy and a certain vector of a plane wave falling onto them, their reflection parameters, like relative backscattering sections and angular scattering characteristic of an anisotropic body are the same as those for isotropic bodies of similar size, shape and elasticity.